Cell therapy with human reprogrammed CD8+ T-cells has antimetastatic effects on Lewis lung carcinoma in C57BL/6 mice - Skurikhin, Evgenii G.; Pershina, Olga; Ermakova, Natalia N.; Pakhomova, Angelina; Zhukova, Mariia; Pan, Edgar S.; Sandrikina, Lyubov A.; Widera, Darius; Kogai, Lena; Kushlinskii, Nikolai; Kubatiev, Aslan A.; Morozov, Sergey G.; et al. (International journal of molecular sciences)
Using a model of Lewis lung carcinoma (LLC) in vitro and in vivo, we previously demonstrated increased antitumor activity in CD8+ T-cells reprogrammed with an MEK inhibitor and PD-1 blocker. In this follow-up study, we carried out the reprogramming of human CD8+ T-cells (hrT-cell) using the MEK inhibitor and PD-1 blocker and targeted LLC cells. The effects of hrT-cell therapy were studied in a mouse model of spontaneous metastasis of a solid LLC tumor. We found antimetastatic activity of hrT-cells, a decrease in the number of cancer cells and cancer stem cells in the lungs, and an increase in the number of T-cells in the blood (including effector T-cells). Thus, reprogramming of human CD8+ T-cells with an MEK inhibitor and PD-1 blocker with targeted training by tumor target cells is a potential platform for developing a new approach to targeted lung cancer therapy.